2022
DOI: 10.1039/d2cc02181a
|View full text |Cite
|
Sign up to set email alerts
|

A base-free copper-assisted synthesis of C2-symmetric spirotelluranes and biaryls based on divergent stoichiometry of Na2Te

Abstract: A one pot Cu(I)-assisted synthetic methodology has been developed for the preparation of biologically important C2-symmetric spirodiaza, benzyloxy, benzoxytelluranes from 2-bromo-N-aryl benzamides, benzyl alcohols, and benzoic acid by using tellurium...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 63 publications
1
6
0
Order By: Relevance
“…Products 11 and 10 bis were crystallized by slow evaporation of a CH 2 Cl 2 /AcOEt solution. Similar to what shown in the literature, [44, 45] the crystal structure of spiro derivative 11 depicts two bicyclic moieties being almost completely perpendicular to each other and connected through the Te‐atom forming a heterocyclic spiro product ( Figure 3 ,a ). By calculating the Electrostatic Surface Potential (ESP) map of 11 , two σ ‐holes having similar values are depicted on the Te(IV) atom ( Figure 3 ,b ).…”
Section: Resultssupporting
confidence: 79%
“…Products 11 and 10 bis were crystallized by slow evaporation of a CH 2 Cl 2 /AcOEt solution. Similar to what shown in the literature, [44, 45] the crystal structure of spiro derivative 11 depicts two bicyclic moieties being almost completely perpendicular to each other and connected through the Te‐atom forming a heterocyclic spiro product ( Figure 3 ,a ). By calculating the Electrostatic Surface Potential (ESP) map of 11 , two σ ‐holes having similar values are depicted on the Te(IV) atom ( Figure 3 ,b ).…”
Section: Resultssupporting
confidence: 79%
“…Synthesis of 2‐ N ‐(quinolin‐8‐yl)benzamide phenyl tellurides : In an oven‐dried 10 mL round bottom flask, 2‐iodo‐2‐ N ‐(quinolin‐8‐yl)benzamide [10a] (374 mg, 1.0 equiv, 1.0 mmol) was taken with diaryl ditelluride (213 mg, 0.52 equiv, 0.52 mmol), CuI (19 mg, 0.1 equiv, 0.1 mmol) and Mg (49 mg, 2.0 equiv, 2.0 mmol) in 5.0 mL of DMF under argon atmosphere at room temperature for 1 h. The progress of the reaction is monitored by TLC. After completion of the reaction, the reaction mixture was poured into the brine solution, then extracted with ethyl acetate (100 mL×3) and washed with water 100 mL x 3.…”
Section: Methodsmentioning
confidence: 99%
“…15 On the other hand, a few compounds with tellurium, another chalcogen but a higher-period element, as a redox active center have also been reported as GPx mimics. 16 Recently, our group reported that a water-soluble telluride, ( S )-tetrahydrotellurophen-3-amine ( 4 ), and its organic solvent-soluble derivative ( 5 ) significantly promoted the oxidation of RSH by peroxides to RSSR through a GPx-like catalytic cycle (Fig. 2A).…”
Section: Introductionmentioning
confidence: 97%